Patient‐reported outcome measuring tools in cataract surgery: Clinical comparison at a tertiary hospital. Issue 12 (December 2016) - Fung, Simon S.M.; Luis, Joshua; Hussain, Badrul; Bunce, Catey; Hingorani, Melanie; Hancox, Joanne
Abstract : Purpose : To assess the performance of patient‐reported outcome measure questionnaires and determine their appropriateness for routine use in cataract patients. Setting : Moorfields Eye Hospital, London, United Kingdom. Design : Prospective cohort study. Methods : Patients having cataract surgery between February and March 2013 were recruited. The following 4 questionnaires—Catquest‐9SF, EuroQol 5‐dimensions questionnaire (EQ‐5D) and visual analog scale (EQ‐VAS), National Eye Institute Socioemotional Scale (NEI‐SES), and short‐form Visual Function Index (VF‐8R)—were completed preoperatively and 3 weeks and 3 months postoperatively. The questionnaires' performances were then compared. The paired Student t test and Pearson correlations were used for statistical analysis. Results : One hundred twenty‐two patients were recruited; 67.2% and 61.8% completed 3‐week and 3‐month follow‐up, respectively. The changes in the mean scores for the Catquest‐9SF, EQ‐5D, EQ‐VAS, NEI‐SES, and VF‐8R at 3 weeks were 120.86% ( P < .0001), 1.61% ( P = .61), 3.37% ( P = .09), 16.12% ( P = .12), and 61.76 % ( P < .0001), respectively. At 3 months, the changes were 162.42% ( P < .0001), 4.54% ( P = .16), 4.84% ( P = .09), 54.63% ( P < .0001), and 87.55% ( P < .0001), respectively. Correlations between patient‐reported outcome measure questionnaires and visual acuity measures were variable and weak at best. Conclusions : It is feasible to assess patient‐reported outcomes in cataract surgery as part of routine clinical practice. In addition, visual acuity might not fully reflect patients' visual function. Clinicians should consider using patient‐reported outcome measure questionnaires to facilitate surgical decision‐making and outcome monitoring. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.